2023
DOI: 10.1108/ccij-05-2023-0066
|View full text |Cite
|
Sign up to set email alerts
|

When relational transparency backfires: examining the various impacts of authentic leadership on employee trust during the COVID-19 pandemic

Qi Zheng,
Chuqing Dong,
Yafei Zhang

Abstract: PurposeThis study examines how the different attributes of authentic leadership influence trust and employee organization fit and how such influences differ by gender and the level of positions during the COVID-19 pandemic.Design/methodology/approachThe study employed a survey to examine US employees' perceptions toward different attributes of authentic leadership during the COVID-19 pandemic.FindingsThe study showed that self-awareness, balanced processing and internalized moral perspective positively relate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In the past three years, CCIJ has increased the publication of EDI/DEI topics by publishing works in a wider area of equality such as gender quotas (Lefley and Janecek, 2023, Hamplová et al , 2022), female journalists and their leadership experiences (Cunha and Lúcio Martins, 2023), female empowerment and internal communication (Li et al ., 2023), gender and the office culture (Polić and Holy, 2021; Tripathi et al ., 2023), femvertising (Lima and Casais, 2021), gender and leadership (Zeler et al ., 2022; Zheng et al ., 2023, Meng and Neill, 2023), CSA and gender equality (Marschlich and Bernet, 2024), JEDI issues and media irresponsibility (Painter and Sahm, 2023), CSR and gender (Painter et al ., 2022), and these are just articles published during my editorship and excluding some special issue articles. Therefore, CCIJ is emerging as a journal that increasingly publishes equality scholarship in corporate communication, contributing towards knowledge creation in this field as well as widening participation and bringing inclusivity to scholarship by opening doors to equality scholars in corporate communication.…”
mentioning
confidence: 99%
“…In the past three years, CCIJ has increased the publication of EDI/DEI topics by publishing works in a wider area of equality such as gender quotas (Lefley and Janecek, 2023, Hamplová et al , 2022), female journalists and their leadership experiences (Cunha and Lúcio Martins, 2023), female empowerment and internal communication (Li et al ., 2023), gender and the office culture (Polić and Holy, 2021; Tripathi et al ., 2023), femvertising (Lima and Casais, 2021), gender and leadership (Zeler et al ., 2022; Zheng et al ., 2023, Meng and Neill, 2023), CSA and gender equality (Marschlich and Bernet, 2024), JEDI issues and media irresponsibility (Painter and Sahm, 2023), CSR and gender (Painter et al ., 2022), and these are just articles published during my editorship and excluding some special issue articles. Therefore, CCIJ is emerging as a journal that increasingly publishes equality scholarship in corporate communication, contributing towards knowledge creation in this field as well as widening participation and bringing inclusivity to scholarship by opening doors to equality scholars in corporate communication.…”
mentioning
confidence: 99%
“…Zheng, Q. et al, When relational transparency backfires: examining the various impacts of authentic leadership on employee trust during the COVID-19 pandemic Zheng et al (2024) conducted an online survey with USA employees to examine the influence of attributes associated with authentic leadership during the COVID-19 pandemic. Through structural equation modeling, they found that self-awareness, balanced processing and internalized moral perspective can positively affect employee-organization fit, and both selfawareness and balanced processing are significantly associated with trust in the employer.…”
mentioning
confidence: 99%